Pelaksanaan Hak Keperdataan Anak dari Orang Tua Putus Perkawinan Karena Talak - Jalil, Siti Misnar Abdul; Hakim, Guswan; Karmila, Karmila (Universitas Batanghari Jambi, 2022)
Child protection, among others, is regulated by the provisions of the Convention on the Rights of the Child ratified by the Government of Indonesia through Presidential Decree Number 36 of 1990 which states the general principles of child protection, namely nondiscrimination, the best interests of children, survival and growth and development, and respect for children's participation. These principles are also contained in the provisions of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection established by the government so that children's rights can be implemented in Indonesia. Thus Civil rights for children whose parents are divorced because of talak according to the Indonesian legal system have obtained guaranteed legal protection. and The implementation of the civil rights of children of parents who break up from marriage because of talak in the Religious Court cannot be implemented as it should be because in the reality of the application of the law, the civil rights of children are only in the form of a living. The divorce of parents is a scourge for their children who should get full affection from both. A child has basic rights as stated in article 2 of Law number 4 of 1979 concerning child welfare.